Organosolv Pulping Batang Sawit Bebas Pati - Febryanto Febryanto; Zulfansyah Zulfansyah; Zuchra Helwani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Oil palm trunk are solid waste with considerable potential and have not been used optimally. Oil palm trunk can be used as raw materials for fiber-based industries such as the pulp and paper industry, starch industry, and other timber industries. The objectives of this research is to obtain the characteristics of pulp (yield, alpha cellulose and lignin of pulp) and studied the effect of cooking time, temperature, and solid to liquid ratio on the pulp produced. Pulping was performed on a rocking digester with 30 grams of oil palm trunk powder starch free, formic acid as a solvent with reaction temperature (110 °C, 130°C and 150 °C), reaction time (60 minutes, 120 minutes and 180 minute), liquid-solid ratio (10:1 b/b) catalyst H2SO4 0,1% wt. The result showed yield pulp of = 32,78-38,99%, lignin pulp of = 7,22-9,22% and alpha cellulose of 92,46-94,85%. The cooking time and temperature has the most influence the characteristics and response of the pulp. Keywords : formic acid, oil palm trunk, organosolv pulping